Data Mining Using PAFI (International Journal of Engineering and Computer Science, 2014)
Data mining is the process of extracting patterns from data. Data mining is becoming an increasingly important tool to transform this data into information. It is commonly used in a wide range of profiling practices, such as marketing, surveillance, fraud detection and scientific discovery. Aim is to make such an application which has lots of inbuilt features and functions, so that many tasks can be performed on same platform, so as to save time, and also enable in curbing cost with the use of technology. At the end our goal is to come up with a good system, well-computerized and embedded with the latest technology in order to give a better service to customers, give a competitive edge to the business.